Impact of Rain Attenuation in Borneo using Free Space Optics Propagation - Tauffiq, Khirham; Abdul Rahman, Kram; Sahari, S.K.; Nurdiani, Zamhari; Tamrin, K. F. (2021)
In recent years, Free Space Optics (FSO) communication provides attractive bandwidth enhancement with unlicensed bands worldwide spectrum. However, the link capacity and availability are the major concern in the different atmospheric conditions. The reliability of the link is highly dependent on weather conditions that attenuate the signal strength. In the tropical region specifically in Borneo Sarawak, rain is the dominant weather that act as the limiting factor to FSO performance. Hence, this study highlights on the impact of rain attenuation to the performance of FSO communication system. The finding is based on atmospheric model and performed through the simulation of OptiSystem software. The design of parameters in the simulation involves iteration of wavelengths, size of transmitter and receiver aperture and beam divergence angle. The simulation result shows longer wavelength 1550nm is much better than 785nm. The 0.25m of receiver aperture and transmitter aperture at 0.05m can reduce the loss. Narrow beam divergence angle can reduce the power consumption and maintain the high power at receiver. The analysis indicates that proposed FSO communication system is capable to withstand the attenuation from rain weather.